Mineralogical impact on the compaction of residual gabbro soils in the construction of Platinum Tailings Storage Facilities - Dippenaar, Matthys Alois (University of Pretoria, 2024)
Dissertation (MSc (Engineering Geology))--University of Pretoria, 2023.